PENGARUH MODAL TERHADAP OMZET PENJUALAN: PERAN BIAYA PEMASARAN SEBAGAI VARIABEL MODERATING - Sriyanto, Sriyanto (STIE Atma Bhakti, 2020)
This study aims to analyze the effect of capital and marketing costs on sales turnover and the effect of capital on sales turnover moderated by marketing costs. Sample of this study are 67 entrepreneurs of culinary in Tasikmadu District Karanganyar Regency, using purposive sampling technique. Data analysis using multiple linear regression and Absolute Difference Test. The conclusion of hypothesis test result (1) capital and marketing cost have significant effect on sales turnover. (2) Marketing costs can moderate that reinforce the effect of capital on sales turnover.